Enhancing Teacher Competency: Strategies and Patterns at Siritham Wittaya School - Areepen Sengsalong; Lia Yuliana (STAI Hubbulwathan Duri, 2025)
Enhancing teacher competence is essential for improving educational quality. This study investigates effective planning, implementation, and evaluation patterns for teacher competency development at Sirithamwittaya School, a junior secondary school in Southern Thailand. A qualitative phenomenological approach was employed to explore the experiences of principals and teachers. Data were collected through observations, interviews, and document analysis to identify key patterns in teacher development. Three major patterns emerged. Planning involves structured collaboration through meetings among principals, teachers, and education staff, fostering a shared vision. Implementation utilizes diverse professional development methods, including training seminars, workshops, material writing training, and ICT training, to enhance teachers' skills. Evaluation is systematic, incorporating activity monitoring, collaborative problem-solving, and teacher recognition to maintain motivation and commitment. Findings underscore the significance of a collaborative approach and systematic evaluation in teacher development. Effective planning ensures alignment with educational goals, diverse implementation strategies enhance professional growth, and structured evaluation reinforces continuous improvement. This study suggests that the identified patterns can serve as a model for other schools seeking to enhance teacher competence and improve educational outcomes. Further research could explore their application in different educational contexts.